Effect of Micture of Tomato Porridge with Sweet Potato Juice and Potassium Sorbat Concentration on the Quality of Papaya Sauce - Sri Novita Sari; Ismed Suhaidi; Rona J. Nainggolan (Jurnal Rekayasa Pangan dan Pertanian, 2015)
The aim of this research was to investigate the effect of mixture of tomato porridge with sweet potato juice and potassium sorbat concentration on the quality of papaya sauce. The research had been performed using factorial completely rendomized design (CRD) with two factors, i.e; mixture of tomato porridge with sweet potato juice (A)=(40:10%), (30:15%), (30:20%), (25:25%) with 50% papaya porridge respectively and potassium sorbat concentration (S)=(0%), (0,1%), (0,2%), (0,3%). Parameters analyzed were moisture content, ash content, total acid, vitamin C content, total soluble solid, viscosity and organoleptik of color, smell, taste. The results showed that mixture of tomato porridge with sweet potato juice had highly significant effect on moisture content, ash content, total acid, vitamin C content, total soluble solid, viscosity and organoleptic value (color, smell, taste). The potassium sorbat concentration had highly significant effect on moisture content, ash content, total acid, vitamin C content, viscosity, and organoleptic values. The intraction of mixture of tomato porridge with sweet potato juice and potassium sorbat concentration had significant effect on total acid and had nosignificant effect on moisture content, ash content, vitamin C content, total soluble solid, viscocity and organileptic values. The (A3)=(30:20%) tomato porridge with sweet potato juice (S2)=(0,1%) potassium sorbat concentration produced better and more acceptable quality of the sauce. Keyword : papaya, potassium sorbat, sauce, sweet potato, tomato